GPU Ray Tracing. - Parker, Steven G.; Friedrich, Heiko; Luebke, David; Morley, Keith; Bigler, James; Hoberock, Jared; McAllister, David; Robison, Austin; Dietrich, Andreas; Humphreys, Greg; McGuire, Morgan; Stich, Martin (Communications of the ACM, 2013)
The NVIDIA® OptiX ray tracing engine is a programmable system designed for NVIDIA GPUs and other highly parallel architectures. The OptiX engine builds on the key observation that most ray tracing algorithms can be implemented using a small set of programmable operations. Consequently, the core of OptiX is a domain-specific justin- time compiler that generates custom ray tracing kernels by combining user-supplied programs for ray generation, material shading, object intersection, and scene traversal. This enables the implementation of a highly diverse set of ray tracing-based algorithms and applications, including interactive rendering, offline rendering, collision detection systems, artificial intelligence queries, and scientific simulations such as sound propagation. OptiX achieves high performance through a compact object model and application of several ray tracing-specific compiler optimizations. For ease of use it exposes a single-ray programming model with full support for recursion and a dynamic dispatch mechanism similar to virtual function calls.